Local–overall interactive buckling behaviour of 800 MPa high-strength steel welded H-section members under axial compression. (July 2021) - Cao, Xianlei; Zhong, Rui; Xu, Yong; Cheng, Chao; Liu, Shitong; Chen, Zongping; Kim, Seung-Eock; Kong, Zhengyi
Abstract: In this study, three different types of columns (i.e. columns with a low width-to-thickness ratio of the plates, columns with a high height-to-thickness ratio of the web, and columns with a high width-to-thickness ratio of the flange) are designed to investigate the buckling behaviour of welded H-section columns fabricated from 800 MPa high-strength steel (HSS). Different buckling behaviours are established, including the load–axial displacement curves, relationships between the local out-of-plane displacement and overall lateral displacement, and ultimate loads of the columns. Current specifications, such as ANSI/AISC and Eurocode 3, are evaluated using the experimental results of this study. It is concluded that ANSI/AISC and Eurocode 3 slightly underestimate the ultimate load of 800 MPa HSS welded H-section members under axial compression. Numerical analyses are performed to estimate the buckling behaviours of 800 MPa HSS welded H-section members under axial compression, and the model is verified using the experimental results in this study. The effects of several parameters (i.e. the slenderness ratio, width-to-thickness ratio of the flange, and height-to-thickness ratio of the web) on the buckling behaviour are investigated. Finite element analyses are carried out for 94 different models, and a more accurate model for estimating the ultimate load of welded H-section members fabricated from 800 MPa HSS is developed. Existing experimental data for HSS columns are collected, and reliability analyses are performed for ANSI/AISC, Eurocode 3, and the proposed model. Highlights: The ratio of σ u ∕ f y decreases as the width–thickness ratio increases. Current specifications are slightly underestimated for estimating the ultimate load. A more accurate model for estimating the ultimate load is recommended.